Sosialisasi Sertifikasi Halal Bagi Pelaku UMKM Di Pantai Depok Kabupaten Bantul - Elza Qorina Pangestika; Tommy Satriadi Nur Arifin (Jurnal Kabar Masyarakat, 2024)
Issuance of Minister of Religion Regulation No. 20 of 2021 on September 14 2021 concerning halal certification for MSEs requires all business actors to process their business products in accordance with Islamic law and have proof of a halal certificate. In terms of implementation, this policy certainly faces various problems, especially those felt by MSEs, including at Depok Beach, Bantul Regency. The aim of this community service activity is to increase knowledge and application of halal certification for MSMEs in Depok Beach, Bantul Regency. The implementation method for this community service activity uses the method of visiting the community, then providing socialization one by one. The output of this community service activity is in the form of activity videos, news coverage on campus and LLDikti websites, as well as accredited national journals.